1991
DOI: 10.12693/aphyspola.80.445
|View full text |Cite
|
Sign up to set email alerts
|

Magnetooptical Properties of Pb1-xMnxSe p-n Junctions

Abstract: The first experimental evidence of the magnetic quantum oscillation in the photovoltaic effect of Pb1-x Mnx Se p-n junctions is reported. The p-n junctions were obtained in Pb1-x Mnx Se crystals with manganese content ,0 < x < 0.08 by introducing Cd donors by diffusion. Measurements were performed between 5-85 K and in the presence of the magnetic field 0-7 T in the Faraday and Voigt configurations of the incident infrared radiation of various photon energies in the vicinity of the energy gap of a Pb1-x Mnx Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1992
1992
2009
2009

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…5 This is expected to bring forth new vistas to the optical studies of these materials. Several studies have been reported on excitonic [6][7][8][9][10][11] and some on internal Mn-PL intensity 12,13 as functions of magnetic field and temperature. [14][15][16] However, while the sp-d exchange interaction is known to lead to magnetic ordering in DMS, 4,5,17 no studies to the best of our knowledge have been reported that show effect of magnetic ordering on internal Mn-PL emission.…”
Section: Introductionmentioning
confidence: 99%
“…5 This is expected to bring forth new vistas to the optical studies of these materials. Several studies have been reported on excitonic [6][7][8][9][10][11] and some on internal Mn-PL intensity 12,13 as functions of magnetic field and temperature. [14][15][16] However, while the sp-d exchange interaction is known to lead to magnetic ordering in DMS, 4,5,17 no studies to the best of our knowledge have been reported that show effect of magnetic ordering on internal Mn-PL emission.…”
Section: Introductionmentioning
confidence: 99%